GEOMORFOLOGIA DO TRAJETO ENTRE CAMPO GRANDE E CORUMBÁ - BRANDÃO, Alessandro Rodrigues de Lima; MONTEIRO, Ana Maria Guimarães; SILVA, Carlos Juliano Fonseca da; SANTOS, Gabriel Ítalo Martins dos; MARTINEZ, Maria Luísa Gonçalves (ANAIS DO ENIC, 2020)
-